Determinação estrutural do modelo mutante da cisteína protease do Theobroma Cacao por modelagem comparativa e cálculos QM/MM - Andrade, Deyse Valverde Gomes de (2009)
The culture of cacao in Brazil was highly harmed by Moniliophthora perniciosa, the fungus that causes witches' broom disease of cocoa. This disease decreases significantly the cocoa production. An important strategy for control of the witches’ broom is the molecular study of the interaction between cacao-M. perniciosa. However, there is little information about of the mechanism of molecular interaction involved in resistance/vulnerability of cacoa tree. To address this problem, the Genome Project showed genes of cysteine protease involved in the mechanism of resistance/vulnerability. Cysteine protease is expressed during the process of the maturation of the seed and it is present in necrofitics period of the disease. Furthermore, proteases have a wide application in feed products, detergents and pharmaceutical industries. This work constructed the 3D structure of the cysteine protease of T. cacao by comparative modeling. Thus, the primary sequence of the cysteine protease of T. cacao was submitted to BLASTp obtaining the protein 1PCI|A with 36% of structural similarity as such. Below, three models were constructed (dv1, dv2 and dv3), which were refined and validated by AMBER 9.0 and PROCHECK software, respectively. Among these models, dv1 showed a better Ramachandran Plot with 95% of amino acids in favorable energy region. The final model consists of 171 amino acids, formed by 2693 atoms linked by 2719 chemical bonds. The 3D structure of this enzyme has 7 α-helix, 23 turns and 2 β-sheets. The region of the conserved active site is represented by residues Cys25 and His159. From this model, a mutant model was then generated by replacing His159/Gly. This also was evaluated showing similar dv1 characteristics. Studies of the interaction between the mutant structure with the metal ions +2, Cu+1, Cu+2 and Cd+2 were carried out by QM/MM approach implemented in Gaussian 03W. As a result, the mutant protein is able to complex with all of them, and showed selective for Cd+2 with -59801 x 103 kcal/mol. Therefore this study suggests that changes in the sequence of the cysteine protease of T. Cacao can lead to the development new products of commercial interest.